1994
DOI: 10.1111/j.1469-7610.1994.tb02302.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric Disorder in Deaf and Hearing Impaired Children and Young People: A Prevalence Study

Abstract: Psychiatric screening questionnaires for deaf children and adolescents were piloted in a group of 62 children, aged 11-16 years, attending a residential school. The questionnaires, Parent's Checklist (PCL) and Teacher's Checklist (TCL) were then used to screen a group of 93 children attending one Deaf School and three Hearing Impaired Units (HIU). Psychiatric assessments were conducted with a highly structured diagnostic interview, the Child Assessment Schedule (CAS). The interview with signing deaf children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
94
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 18 publications
5
94
0
1
Order By: Relevance
“…The survey findings indicated three important health-related disparities between the deaf people who took the survey and the hearing people who live in the same county including: 1) increased rates of cardiovascular risks including obesity; 2) increased risks for intimate partner violence; and 3) increased reports of suicidal attempts . These findings are consistent with other previous studies indicating that deaf people appear to be experiencing significant disparities in their health and mental health literacy and outcomes (Margellos-Anast et al, 2006, Maxwell-McCaw, 2001Hindley et al, 1994). Whereas these surveys and studies have helped to identify specific health disparities that deaf people experience, they did not include items that explored the reasons why deaf people might be experiencing these health disparities.…”
Section: Pertinent Socioecological Barriers and Issues Affecting Deafsupporting
confidence: 80%
“…The survey findings indicated three important health-related disparities between the deaf people who took the survey and the hearing people who live in the same county including: 1) increased rates of cardiovascular risks including obesity; 2) increased risks for intimate partner violence; and 3) increased reports of suicidal attempts . These findings are consistent with other previous studies indicating that deaf people appear to be experiencing significant disparities in their health and mental health literacy and outcomes (Margellos-Anast et al, 2006, Maxwell-McCaw, 2001Hindley et al, 1994). Whereas these surveys and studies have helped to identify specific health disparities that deaf people experience, they did not include items that explored the reasons why deaf people might be experiencing these health disparities.…”
Section: Pertinent Socioecological Barriers and Issues Affecting Deafsupporting
confidence: 80%
“…There is robust evidence that delayed language acquisition in either modality increases the risk of mental health problems, and such delays occur in many deaf children. 8 Hearing parents with deaf children (90-95%) are less likely to encounter the world of deafness and as such are more likely to choose a predominantly oral approach to communication, despite the risk that this might result in a significantly delayed acquisition of language in the child. 9 In contrast, deaf children with deaf parents have natural access to sign language as their first language and subsequently have typical language acquisition patterns and fewer mental health problems.…”
Section: Declaration Of Interestmentioning
confidence: 99%
“…The incidence of mental health problems in deaf children/young people is around 1.5 times greater than among their hearing counterparts. 25 In adulthood, although the incidence of major psychoses is broadly consistent with that among hearing people, the prevalence of depressive disorders and anxiety is significantly higher (33% of the Deaf population vs. around 20% of the hearing population). 26 Studies have demonstrated the inaccessibility of health services to Deaf BSL users, [27][28][29][30] including mental health services, resulting in late diagnoses and loss of benefit from early preventative interventions.…”
Section: Deaf People and Mental Healthmentioning
confidence: 91%